External Quality Assessment Pilot Study for the detection of Candida auris - Veríssimo, Cristina (2022)
Candida auris, identified for the first time in 2009, is a multi-resistant emergent yeast that causes nosocomial outbreaks all over the world. This species can be misidentified with other Candida species, if the method used for yeasts’ identification (biochemical / mass spectrometry (MALDI-TOF-MS) has not been updated in order to contain the profile of this species. Aiming to raise the awareness about the risk of misidentification associated to this species, the Portuguese External Quality Assessment Program (PNAEQ), in collaboration with the National Reference Laboratory for Parasitic and Fungal Infections of the National Institute of Health Dr. Ricardo Jorge, organized a pilot study in 2020 to evaluate the ability of Portuguese clinical microbiology laboratories to correctly identify C. auris.